On-admission SARS-CoV-2 RNAemia as a single potent predictive marker of critical condition development and mortality in COVID-19 - Miki, Shoji; Sasaki, Hiroaki; Horiuchi, Hiroshi; Miyata, Nobuyuki; Yoshimura, Yukihiro; Miyazaki, Kazuhito; Matsumura, Takayuki; Takahashi, Yoshimasa; Suzuki, Tadaki; Matano, Tetsuro; Kawana-Tachikawa, Ai; Tachikawa, Natsuo (PloS one, 2021)
This study aimed to clarify how SARS-CoV-2 RNAemia is related to COVID-19 critical condition development and mortality in comparison with other predictive markers and scoring systems. This is a retrospective cohort study conducted at Yokohama Municipal Citizen's Hospital and National Institute of Infectious Diseases. We recruited adult patients with COVID-19 admitted between March 2020 and January 2021. We compared RNAemia with clinical status on admission including scoring systems such as the 4C Mortality, CURB-65, and A-DROP, as well as the C.sub.t value of the nasopharyngeal PCR, in predicting COVID-19 mortality and critical condition development. Of the 92 recruited patients (median age, 58; interquartile range, 45-71 years), 14 (14.9%) had RNAemia. These patients had an older age (median, 68 years vs. 55.5 years; p = 0.011), higher values of lactated dehydrogenase (median, 381 U/L vs. 256.5 U/L, p < 0.001), C-reactive protein (median, 10.9 mg/dL vs. 3.8 mg/dL; p < 0.001), D-dimer (median, 2.07 [mu]g/mL vs. 1.28 [mu]g/mL; p = 0.015), lower values of lymphocyte (median, 802/[mu]L vs. 1007/[mu]L, p = 0.025) and C.sub.t of the nasopharyngeal PCR assay (median, 20.59 vs. 25.54; p = 0.021) than those without RNAemia. Univariate analysis showed RNAemia was associated with mortality (odds ratio [OR], 18.75; 95% confidence interval [CI], 3.92-89.76; area under the receiver operating characteristic curve [AUC], 0.7851; p = 0.002) and critical condition (OR, 72.00; 95% CI, 12.98-399.29; AUC, 0.8198; p < 0.001). Plus, multivariate analysis also revealed the association of RNAemia with critical condition (adjusted OR, 125.71; 95% CI, 11.47-1377.32; p < 0.001). On-admission SARS-CoV-2 RNAemia is a potent predictive marker of COVID-19 critical condition and mortality. The adjusted OR for critical condition was as high as 125.71.